MODERASI BERAGAMA DALAM GEGURITAN NENGAH JIMBARAN - Ni Made Ari Dwijayanthi; Krisna S Yogiswari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Geguritan Nengah Jimbaran as a material object in this study is a traditional Balinese literary work written by Cokorda Mantuk Ring Rana. This study uses a qualitative approach that focuses on finding the meanings of religious moderation in the Geguritan Nengah Jimbaran text. The hermeneutic method is applied to understand and interpret the meaning and intention of Cokorda Mantuk Ring Rana in his writing. Based on the analysis carried out at Geguritan Nengah Jimbaran, it shows Balinese people are indeed dominated by Hindus but they have a great tolerance and are able to live harmoniously side by side among different faith during the reign of Cokorda Mantuk Ring Rana. It can be concluded that religious tolerance as one of the spirits of religious moderation has long been present and has become a habit of Balinese people today. Key words: religious moderation, tolerance, Geguritan Nengah Jimbaran